Prevalence of cancer survivors in the United States - Tonorezos, Emily; Devasia, Theresa; Mariotto, Angela B; Mollica, Michelle A; Gallicchio, Lisa; Green, Paige; Doose, Michelle; Brick, Rachelle; Streck, Brennan; Reed, Crystal; de Moor, Janet S (JNCI : Journal of the National Cancer Institute, 2024)
With aging of the population and improvements in diagnosis, treatment, and supportive care, the number of cancer survivors in the United States has increased; updated prevalence estimates are needed. Cancer prevalence on January 1, 2022, was estimated using the Prevalence Incidence Approach Model, utilizing incidence, survival, and mortality. Prevalence by age decade, sex, and time from diagnosis was calculated. The percentage of cancer survivors in the projected US population by age and sex was calculated as the ratio of the sex-specific projected prevalence to the sex-specific projected US population. There were an estimated 18.1 million US cancer survivors as of January 1, 2022. From 2022 to 2030, the number of US cancer survivors is projected to increase to 21.6 million; by 2040, the number is projected to be 26 million. Long-term survivors are highly prevalent; in 2022, 70% of cancer survivors had lived 5 years or more after diagnosis, and 11% of cancer survivors had lived 25 years or more after diagnosis. Among all US females aged 40-54 years, 3.6% were cancer survivors; among females aged 65-74 years, 14.5% were cancer survivors; among females aged 85 years and older, 36.4% were cancer survivors. Among all US males aged 40-54 years, 2.1% were cancer survivors; among males aged 65-74 years, 16% were cancer survivors; and among those aged 85 years and older, 48.3% were cancer survivors. Cancer survivors are growing in number. In the United States, most cancer survivors are long-term and very long-term survivors, representing a substantial proportion of the US population.